Evaluating rational and healthy use options for small pelagic fish species in sub-Saharan Africa - Bunting, Stuart; Thiao, Djiga; Ahern, Molly; Ansah, Yaw B; Ward, Ansen; Wesana, Joshua; Yossa, Rodrigue; Westlund, Lena (Springer, 2024)
Small pelagic fish species (SPFS) from marine waters off Central-West Africa and North-West Africa and the African Great Lakes Region in Eastern Africa and associated value chains sustain several million livelihoods. Catches are used for direct human consumption, to produce fishmeal and fish oil for animal feeds and to manufacture value-added products. SPFS constitute a valuable source of micronutrients, fatty acids and protein that could help alleviate malnutrition and food insecurity in sub-Saharan Africa. Considering this context, this study aimed to identify and prioritise recommendations concerning SPFS use. Preliminary recommendations came from interviews (n = 122) and focus groups (n = 642) with women and men. Representative stakeholders from Gambia, Ghana, Malawi, Mauritania, Republic of Congo, Senegal, Sierra Leone and Uganda engaged in a Delphi study. Responses were received from 150 and 115 participants in Rounds 1 and 2, respectively. Priority recommendations (Round 2 mean rating >8) included: environmental audits of fishmeal plants, promote health and safety at work, assess health risks, eliminate pollution, locate factories away from residential areas, promote alternative feed ingredients, farmer training and research programmes, enhanced governance, demand assessment, price controls on fish for feed, regular assessment of key fish stocks, assess and monitor fish affordability, consumption and importance in food and nutrition security, promote better handling to avoid food waste, regulate capacity of fishmeal sector. Comprehensive and effective implementation of priority recommendations could ensure that SPFS use can contribute to food and nutrition security and help provide sustainable and healthy diets across sub-Saharan Africa.